Integrasi Autodesk Inventor dan Media 3D PowerPoint Berbasis Animasi Morph Transition dalam Meningkatkan Kompetensi Gambar Teknik Siswa SMK IPT Karangpanas - Ridho Fajar Irsandi; Septian Eko Cahyanto; Kriswanto Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the effect of integrating Autodesk Inventor and Morph 3D PowerPoint on students’ learning outcomes in the Engineering Drawing subject at SMK IPT Karangpanas. A true experimental design with a pretest–posttest control group was employed, involving an experimental class (n = 18) and a control class (n = 19). The test instrument was validated by experts and categorized as “highly feasible,” with strong reliability based on the percentage of agreement. The pretest results showed a significant difference between the two groups; therefore, the learning effectiveness analysis focused on the N-Gain score. Findings indicate that the experimental group achieved medium improvement, whereas the control group showed low improvement. The Mann–Whitney test was used due to the non-normal distribution of the data, resulting in U = 2.000, Z = –5.222, and p = 0.000, confirming a significant difference in the posttest scores between the groups. These results demonstrate that the integration of 3D-based visualization media enhances students’ spatial representation skills more effectively than conventional 2D media. Practically, this study offers an alternative instructional media that vocational teachers can use to clarify object-view concepts and improve the effectiveness of engineering drawing instruction.